Proteomic and transcriptomic screening demonstrates increased mast cell–derived CCL23 in systemic mastocytosis - Söderlund, Stina; Boey, Daryl; van Midden, Wouter; Kjellander, Matilda; Ax, Kajsa; Qian, Hong; Dahlin, Joakim S.; Ungerstedt, Johanna (Journal of allergy and clinical immunology, 2023)
[Display omitted] Systemic mastocytosis (SM) is a heterogeneous group of mast cell–driven diseases diagnosed by bone marrow sampling. However, there are a limited number of available blood disease biomarkers. Our aim was to identify mast cell–derived proteins that could potentially serve as blood biomarkers for indolent and advanced forms of SM. We performed a plasma proteomics screening coupled with single-cell transcriptomic analysis in SM patients and healthy subjects. Plasma proteomics screening identified 19 proteins upregulated in indolent disease compared to healthy, and 16 proteins in advanced disease compared to indolent. Among these, 5 proteins, CCL19, CCL23, CXCL13, IL-10, and IL-12Rβ1, were higher in indolent relative to healthy and in advanced disease compared to indolent. Single-cell RNA sequencing demonstrated that CCL23, IL-10, and IL-6 were selectively produced by mast cells. Notably, plasma CCL23 levels correlated positively with known markers of SM disease severity, namely tryptase levels, percentage bone marrow mast cell infiltration, and IL-6. CCL23 is produced predominantly by mast cells in SM, and CCL23 plasma levels are associated with disease severity, correlating positively with established markers of disease burden, thus suggesting that CCL23 is a specific SM biomarker. In addition, the combination of CCL19, CCL23, CXCL13, IL-10, and IL-12Rβ1 may be useful for defining disease stage.